Dynamic changes occur in the cell wall composition and related enzyme activities during flower development in Rosa damascena - Önder, Sercan; Tonguç, Muhammet; Önder, Damla; Erbaş, Sabri; Mutlucan, Murat (Frontiers in Plant Science, 2023)
The flowering period of oil-bearing rose is short and many physiological processes occur during flower development. Changes in the cell wall composition and associated enzyme activities are important as they allow cells to divide, differentiate and grow. In the present study, changes in seven cell wall components and six cell wall-related enzyme activities at five flower development stages were investigated and the relationships between these parameters and flowering were examined. Ash content did not change between stages I to II but decreased at later stages. Neutral detergent fiber (NDF), acid detergent fiber (ADF) and hemicellulose contents increased after stage I but did not change significantly at the other developmental periods. Total pectin content increased throughout flower development. An “increase–decrease” trend was observed in total cellulose content and a “decrease–increase” pattern in uronic acid content. The activities of both glycosidases (β-galactosidase, β-glucosidase and endoglucanase) and pectinases (pectin lyase, pectin methyl esterase and polygalacturonase) increased until stage IV and decreased significantly at stage V of flower development. Correlation analysis revealed 14 positive and one negative correlation with the studied parameters. Cell wall enzymes showed positive correlations with each other. Principal component analysis (PCA) showed that ADF, NDF and cellulose content were significantly altered at stage II of flower development, and significant changes occurred in all cell wall enzyme activities between stages III and V. Overall, blooming is correlated closely with increased pectin and decreased cellulose contents, and changes in cell wall glucosidase and pectin hydrolysis enzyme activities. These results show that cell wall modifying enzymes are part of the flower development process in oil-bearing rose. Therefore, remodeling of cell wall components in petals is a process of flower development.